Industry and SWOT Analysis as a Basis for Strategy Formulation and Risk Identification at X Cawang General Hospital - Karin Berlian Irene; Posdo Simarmata, Vidi (Universitas Muhammadiyah Pontianak, 2026)
This study examines how industry and SWOT analyses can support strategy formulation and risk identification at RSU X Cawang. Using a qualitative descriptive case study approach, the research applies PESTEL, Porter’s Five Forces, EFAS, IFAS, SFAS, and SWOT analyses. The findings show that the hospital has strong internal capabilities but faces considerable external challenges, particularly regulatory changes, rising operational costs, and increasing competition. The hospital is positioned in Quadrant II, indicating the need for diversification, efficiency, and service innovation strategies. These results provide practical implications for strengthening competitiveness, governance, and long-term organizational sustainability. Keywords: Industry analysis, SWOT analysis, hospital strategy, risk management, service innovation, operational efficiency, healthcare competitiveness, strategic planning